MODEL BUYING DECISION AND REPEAT PURCHASE: PRODUCT QUALITY ANALYSIS (Case Study of Bank Permata Syariah Jakarta KPR Financing Customers) - Phong Thanh Nguyen; Hapzi Ali; Agung Hudaya (Dinasti Publisher, 2019)
Sharia mortgage financing at PT Bank Permata Syariah Business Unit. Targets and achievements of Sharia KPR financing up to August 2018 there is a high enough gap because of not achieving the target. In addition, the ranking of Bank Permata Syariah which is still far below shows that the contribution of mortgage financing has not been high. This is caused by many factors including the financing process and product quality that still needs to be improved so that it affects the Buying decisions and also the repurchase of Bank Permata Syariah mortgage financing . This study aims to determine the effect of process and product quality on Buying and repurchase decisions. The design of this study was explanatory.The sampling technique in this study was the Bank Permata Syariah customers in the South Tangerang Region and filled out the questionnaire using the accidental sampling method but still fulfilled the specified criteria. The sampling technique is purposive sampling with a total population of 150 Permata Bank customers in the South Tangerang Region. By using the Slovin formula, a sample of 100 customers is obtained, the defined margin of error is 10% or 0.10. Quantitative analysis method with SEM analysis tools and Smart PLS and SPSS tools.